Effects of an art therapy Program on the clinical symptomatology of patients with schizophrenia - Yaroska Ceballo Bello; Johnny de Vasconcellos de Freitas; Aline Ferreira Correia (Arteterapia)
In this investigation we designed and applied an art therapy program of twelve sessions, where the participants performed, both freely and guided, two-dimensional graphic expressions with the purpose of reducing the schizophrenia’s clinical symptomatology. It was evaluated in pre and post test sessions using the Social Cognition Scale (GEOPTE) and Positive and Negative Syndrome Scale (PANSS). The quantitative analysis shows difference with statistical significance in only one dependant variable’s components, referred to the Report of Social Cognition by the institution’s health staff. Te results are discussed taking into consideration qualitative information collected in a naturalistic way.